THE DEVELOPMENT OF YOUTH AND WOMEN'S SPORTS IN UZBEKISTAN FROM 1991 TO 2019 (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the reforms aimed at developing youth and women's sports in Uzbekistan from 1991 to 2019 and their outcomes, based on scientific and historical literature and sources. The research also encompasses an analysis of the establishment and regular implementation of the three-tiered sports system: "Universiade" (for university students), "Barkamol Avlod" (for students of secondary specialized educational institutions), and "Umid Nihollari" (for secondary school students). The organization and traditional holding of these competitions are explored within the scope of the study.